Space-time distribution of zooplankton community in an Amazonian artificial coastal lagoon in Bragança, Pará, Brazil - Martins, Adriano Augusto Vilhena; Costa, Rauquírio André Marinho da; Pereira, Luci Cajueiro Carneiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The aim of this study was to report the composition and spatial temporal variation of the zooplanktonic community of the ‘lagoa Salina’, situated in the Caeté river estuary, Pará, Brazil. Samples were collected in three different stations distributed along the logoon through the filtration of 400 l of water in a conical-cilindric plankton net (mesh size of 75 mm). Precipitation data were also recorded. The following species were found: Criptocyclops brevifurca, Ceriodaphnia cornuta, Latonopsis australis and Brachionus sp. The most abundant species was Brachionus sp. and the species most frequent was C. brevifurca. The highest densities were registered during the rainy season and the lowest number of species was observed in the dry season. The seasonality showed an important role on the zooplankton community structure.